Prevalence of Glaucoma in Patients Attending Glaucoma Screening Program: A Cross-Sectional Study, Benghazi, Libya. - S. Altawati, Rehab; A. Elsaeid, Nada; A. Bukhatwa, Samar (Scientific Journal of University of Benghazi, 2025)
Glaucoma, a leading cause of blindness worldwide, glaucoma afflicted 64.3 million people in 2013 and is expected to affect 111.8 million by 2040. For early detection and treatment, it is essential to look into the prevalence of glaucoma and its risk factors. Finding important clinical and demographic indicators of glaucoma in adults screened as part of a public program in Benghazi, Libya, was the goal of this study. During “Glaucoma Week” in February 2024, 366 adult patients were recruited for this cross-sectional study. The participants were divided into three categories: glaucoma suspect (21.0%, n=77), glaucoma unlikely (34.5%, n=126), and confirmed glaucoma (44.5%, n=163). A first-degree relative with glaucoma (OR =2.08, p = 0.016), a history of ocular inflammation (OR = 5.2; p = 0.008), and a higher left-eye intraocular pressure (IOP) (OR = 1.18, p = 0.003) were all significant predictors of confirmed glaucoma, according to logistic regression analyses. In one model, male gender was also a significant predictor (OR = 1.85, p = 0.027). The development of glaucoma was significantly influenced by these factors. In order to improve glaucoma detection in Libya, this study highlighted the significance of targeted screening and monitoring, especially for people with ocular inflammation, a family history of glaucoma, or elevated left-eye IOP.